Risiko Stunting Anak Baduta (7-24 bulan) - Dewi Sri Sumardilah; Antun Rahmadi (Politeknik Kesehatan Tanjung Karang, 2019)
The results of Nutritional Status Monitoring (PSG) showed that the prevalence of stunting 29,6% in 2017. The adverse effects of stunting in toddlers is a disorder of decreased cognitive abilities and learning achievement, decreased immunity, the risk of degenerative diseases. The city of Bandar Lampung is still faced with acute and chronic nutritional problems because the prevalence of stunting in children under five is still high. Therefore, the research conducted in Sukaraja Village, Panjang District, Bandar Lampung City, considering that the Village has the highest population of poverty compared to other villages. The aim of the research is to obtain information about the risk factors for stunting in children under two years (7-24 months) This type of research was observational using case-control design, with a sample of 53 people for the case group and 106 people for the control group where the selection for the case group and controls was done in a simple random manner. Data analysis using chi-square test. The results showed that energy consumption factors (p=0.040), exclusive breastfeeding (p=0.011), history of infectious diseases (p=0.000), history of premature birth (p=0.022), and maternal education level (p=0.029) were related significantly with the incidence of stunting. While protein consumption factors (p=0.283), Zink consumption (p=0.321), Early Breastfeeding Initiation (p=0.538), maternal nutrition status (p = 0.056), maternal age (p=0.438), and distance the age of birth (p=0.188) was not significantly associated with the incidence of stunting of children aged 7-23 months in the Sukaraja Village of Panjang District. Regular home visits by health workers are expected to increase maternal awareness during pregnancy to have a pregnancy checked.